At the heart of the matter: how mental stress and negative emotions affect atrial fibrillation - Leo, Donato Giuseppe; Ozdemir, Hizir; Lane, Deirdre A.; Lip, Gregory Y. H.; Keller, Simon S.; Proietti, Riccardo (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) is the most common form of cardiac arrhythmia, affecting 2-3% of the world's population. Mental and emotional stress, as well as some mental health conditions (e.g., depression) have been shown to significantly impact the heart and have been suggested to act both as independent risk factors and triggers in the onset of AF. In this paper, we review the current literature to examine the role that mental and emotional stress have in the onset of AF and summarise the current knowledge on the interaction between the brain and heart, and the cortical and subcortical pathways involved in the response to stress. Review of the evidence suggests that mental and emotional stress negatively affect the cardiac system, potentially increasing the risk for developing and/or triggering AF. Further studies are required to further understand the cortical and sub-cortical structures involved in the mental stress response and how these interact with the cardiac system, which may help in defining new strategies and interventions to prevent the development of, and improve the management of AF.